Sosialisasi Akses Air Bersih mendukung Sanitasi SD Kelas Jauh Desa Kampung Bunga - Sahriyal, Sahriyal; Nurjayanti, Nurjayanti; Neswita, Nedra; Agustin, Sri; Trisnawati, Lisa; Mauliantino, Bobby (Universitas Pahlawan Tuanku Tambusai, 2026)
Limited access to clean water and adequate sanitation remains a major challenge for remote elementary schools and has a direct impact on students’ health and learning comfort. This Community Service program aimed to provide basic knowledge to teachers and students regarding clean water sanitation standards and to improve their understanding of the implementation of sanitation programs in the school environment. The activities were conducted through educational, participatory, and applicative approaches, including counseling sessions, discussions, active involvement of school members, and the construction of handwashing facilities and simple water filtration systems. The results indicated an improvement in teachers’ and students’ awareness and understanding of the importance of sanitation, the development of clean and healthy living behaviors, and the availability of sanitation facilities that can be utilized sustainably. This program represents a practical effort to support the creation of a healthy, safe, and proper school environment.